18=7c+2-3y

Rewrite the equation as 7c+2-3y=18.

7c+2-3y=18

Subtract 7c from both sides of the equation.

2-3y=18-7c

Subtract 2 from both sides of the equation.

-3y=18-7c-2

Subtract 2 from 18.

-3y=-7c+16

-3y=-7c+16

Divide each term in -3y=-7c+16 by -3.

-3y-3=-7c-3+16-3

Cancel the common factor of -3.

Cancel the common factor.

-3y-3=-7c-3+16-3

Divide y by 1.

y=-7c-3+16-3

y=-7c-3+16-3

Simplify each term.

Dividing two negative values results in a positive value.

y=(7)c3+16-3

Move the negative in front of the fraction.

y=7c3-163

y=7c3-163

y=7c3-163

Solve for y 18=7c+2-3y